BEYOND THE NUT: PIONEERING SUSTAINABLE PRACTICES THROUGH ARECANUT DIVERSIFICATION - Dhimal, Tara; Sharma, Prashanta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The arecanut (Areca catechu), more generally known as the betel nut, holds a very significant place in the cultural and economic lives of several Asian countries. Traditionally used as a masticatory substance, the market for arecanut is threatened by health issues, price fluctuations, and saturation. This paper examines newer usages for arecanut beyond traditional ones so that greater economic benefits could accrue to farmers and other stakeholders. In this paper, we address the current status of the arecanut industry, alternate usage, and strategies for diversification. Drawing from agricultural, economic, and biochemical studies, this paper gives a fair overview of the emerging innovations in the arecanut sector. The findings suggest that diversification into bioactive compounds, pharmaceuticals, agro-waste utilization, and cultural tourism may be substantive regarding economic benefits and sustainability for the arecanut sector.